Congo Style - Sacks, Ruth (University of Michigan Press, 2023)
Congo Style presents a postcolonial approach to discussing the visual culture of two now-notorious regimes: King Leopold II’s Congo Colony and the state sites of Mobutu Sese Seko’s totalitarian Zaïre. Readers are brought into the living remains of sites once made up of ambitious modernist architecture and art in Kinshasa, Democratic Republic of the Congo. From the total artworks of Art Nouveau to the aggrandizing sites of post-independence Kinshasa, Congo Style investigates the experiential qualities of man-made environments intended to entertain, delight, seduce, and impress. In her study of visual culture, Ruth Sacks sets out to reinstate the compelling wonder of nationalist architecture from Kinshasa’s post-independence era, such as the Tower of the Exchange (1974), Gécamines Tower (1977), and the artworks and exhibitions that accompanied them. While exploring post-independence nation-building, this book examines how the underlying ideology of Belgian Art Nouveau, a celebrated movement in Belgium, led to the dominating early colonial settler buildings of the ABC Hotels (circa 1908–13). Congo Style combines Sacks’s practice as a visual artist and her academic scholarship to provide an original study of early colonial and independence-era modernist sites in their African context.